On SCO and EAEU Cooperation - Li. Xin (Международная аналитика)
The paper discusses in detail general prospects and concrete routes of expansion of economic, financial, investment cooperation within SCO, in the author’s opinion this organization should become the main platform for construction of Silk Road Economic Belt.